MENINGKATKAN PRESTASI BELAJAR PKn MELALUI METODE PEMBERIAN TUGAS DAUR ULANG - Rokanah Rokanah (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2015)
The purposes of the study were (1) to describe the civics learning process by giving the recycling task method and (2) to describe an increase of civics students' learning achievement by giving the recycling task. The study was conducted at the first graders of the state elementary school of Tukkerto, Deket – Lamongan, which was designed to classroom action research (PTK) within three cycles. Each cycle was done through four stages: planning, implementation, observation and reflection. The results showed that the learning outcomes of students in the first cycle in the average value of 61.50 with students’ learning mastery of 45.00%, in the second cycle increased to 65.75 with 60.00% completeness, and the third cycle increased to 71.37 with thoroughness 87.50%. These results recommended that the implementation of recycling task can improve civics learning achievement.